2020
DOI: 10.1016/j.molp.2020.01.013
|View full text |Cite
|
Sign up to set email alerts
|

FHY3 and FAR1 Integrate Light Signals with the miR156-SPL Module-Mediated Aging Pathway to Regulate Arabidopsis Flowering

Abstract: In response to competition for light from their neighbors, shade-intolerant plants flower precociously to ensure reproductive success and survival. However, the molecular mechanisms underlying this key developmental switch are not well understood. Here, we show that a pair of Arabidopsis transcription factors essential for phytochrome A signaling, FAR-RED ELONGATED HYPOCOTYL3 (FHY3) and FAR-RED IMPAIRED RESPONSE1 (FAR1), regulate flowering time by integrating environmental light signals with the miR156-SPL mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 72 publications
0
65
1
Order By: Relevance
“…Transgenic plants overexpressing miR156‐resistant versions of SPL3 , SPL4 , SPL5 , SPL10 , and SPL11 ( rSPL3 , rSPL4 , rSPL5 , rSPL10 , and rSPL11 ), respectively, revealed that SPL3, SPL4, and SPL5 proteins promote the adult phase, including flowering (Cardon et al ., 1999; Wu and Poethig, 2006; Shikata et al ., 2009), whereas SPL10 and SPL11 play only minor roles (Huijser and Schmid, 2011). In agreement with this observation, a spl3 spl4 spl5 triple knockout mutant generated via CRISPR/Cas9 flowered significantly later than Col‐0 plants (Xie et al ., 2020). Based on single and double mutant analyses (Shikata et al ., 2009), SPL2, which belongs to the same phylogenetic clade as SPL10 and SPL11, was proposed to have only a weak effect on vegetative phase change (Riese et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic plants overexpressing miR156‐resistant versions of SPL3 , SPL4 , SPL5 , SPL10 , and SPL11 ( rSPL3 , rSPL4 , rSPL5 , rSPL10 , and rSPL11 ), respectively, revealed that SPL3, SPL4, and SPL5 proteins promote the adult phase, including flowering (Cardon et al ., 1999; Wu and Poethig, 2006; Shikata et al ., 2009), whereas SPL10 and SPL11 play only minor roles (Huijser and Schmid, 2011). In agreement with this observation, a spl3 spl4 spl5 triple knockout mutant generated via CRISPR/Cas9 flowered significantly later than Col‐0 plants (Xie et al ., 2020). Based on single and double mutant analyses (Shikata et al ., 2009), SPL2, which belongs to the same phylogenetic clade as SPL10 and SPL11, was proposed to have only a weak effect on vegetative phase change (Riese et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…ft mutant Arabidopsis flowered earlier under incandescent light (Martinez-Zapater & Somerville, 1990) or in TL with far-red LED compared to in TL (Schluepmann et al, unpublished) suggesting that FT is not involved. Signaling was also reported via PHYBregulated PIF4 protein complexes that bind the promoters of miRNA156/172 directly with interference from PHYA-regulated TF (Sánchez-Retuerta et al, 2018;Sun et al, 2018;Xie et al, 2020). In the present study, the highly induced MIKC C turned out a paralogue of SOC1, and miR156/172 steady states were unaltered by the far-red triggered transition to RD in A. filiculoides ( Figure 7B; Supplemental Table 6) suggesting that mechanisms in ferns and seed plant RD are not conserved.…”
Section: Red-dominated Light Suppresses Formation Of Dissemination Stmentioning
confidence: 46%
“…Far-red light responses in Azolla ferns look alike a shade-avoidance syndrome but signal transduction pathways that mediate them in ferns remain largely uncharacterized (Inoue et al, 2017). Pathways causing shade response components are known to use alternative phytochromes and interacting factors (Possart et al, 2013;Xie et al, 2020).…”
Section: Red-dominated Light Suppresses Formation Of Dissemination Stmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic A. alpina lines with reduced miR156 activity or overexpressing the miR156 ‐resistant form of AaSPL15 , flower when vernalised as young seedlings (grown for 2 or 3 wk before vernalisation) (Bergonzi et al ., 2013; Hyun et al ., 2019). We demonstrated that miR172 accumulation increased when A. alpina plants became older, resembling previous studies in Arabidopsis thaliana and other species, a mechanism regulated by SPL9, SPL10 and SPL3/4/5 (Aukerman & Sakai, 2003; Chuck et al ., 2007; Wu et al ., 2009; Xie et al ., 2020). We also established a role for AaTOE2 in reproductive competence and placed AaSPL5 downstream of AaTOE2 (Fig.…”
Section: Discussionmentioning
confidence: 99%